Clinical usefulness of urinary symptoms and urinalysis in diagnosis of Schistosoma haematobium infection in an endemic area in Southern Nigeria: descriptive study - Nwaoha, Chinyere A.; Nwolisa, Emeka C.; Ikejiaku, Udochikwuka P.; Amamilo, Ifeyinwa B.; Ekanem, Emmanuel E. (International Journal of Contemporary Pediatrics, 2024)
Background: Schistosoma haematobium infection occurs worldwide with the largest number of cases seen in sub-Saharan Africa. Most of the infections are acquired during childhood and are linked to urogenital diseases which contributes significantly to morbidity and mortality. A study on the use of urinary symptoms, signs and urinalysis in the diagnosis of S. haematobium infection might aid in providing early, prompt and rapid intervention that will limit associated complications. Methods: The study was a descriptive cross-sectional of 421 children aged 6-12 years in Ohaukwu LGA, Ebonyi State, recruited from four public primary schools using multistage sampling method. Urinary symptoms and signs were obtained using a questionnaire; urine samples were collected for urinalysis and urine microscopy. Simple proportions and odds ratio (CI) were used to analyze the data. Sensitivity, specificity, positive predictive value and negative predictive value were calculated for various symptoms and signs. The data was analyzed with IBM-SPSS 20. Significance was set at p<0.05. Results: The prevalence of S. haematobium infection among school children in Ohaukwu LGA was 30.17%. Visible blood in urine 71.77% and dysuria 70.16% were the predominant symptoms while liver tenderness 8.87% was the most common sign. The sensitivity vs specificity of visible blood in urine and microscopic haematuria were 71.77% vs 94.43% and 100.00% vs 97.21% respectively. Conclusions: Microscopic haematuria alone was highly sensitive and specific and can be a reliable alternative to the gold standard in making diagnosis of S. haematobium infection in children living in this endemic region.